2018
DOI: 10.1126/sciadv.aar5832
|View full text |Cite
|
Sign up to set email alerts
|

A simple electron counting model for half-Heusler surfaces

Abstract: A simple model explains the atomic and electronic structure of Heusler surfaces, supported by experiments and first-principles theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
(64 reference statements)
3
21
1
Order By: Relevance
“…There is a magnetic interaction between the two X atoms, and they are coupled ferromagnetically or antiferromagnetically with the Y atom. [32] They form a covalent interaction through hybridization with the s and p states of the main-group element Z. The bonding states are well confirmed by the similarly extended X-ray absorption fine structure (EXAFS) spectroscopy between the Co 2 MnGa bulk single crystal and Co foil (Figure S1).…”
Section: Synthesis and Structure Of Heusler Single Crystalsmentioning
confidence: 57%
“…There is a magnetic interaction between the two X atoms, and they are coupled ferromagnetically or antiferromagnetically with the Y atom. [32] They form a covalent interaction through hybridization with the s and p states of the main-group element Z. The bonding states are well confirmed by the similarly extended X-ray absorption fine structure (EXAFS) spectroscopy between the Co 2 MnGa bulk single crystal and Co foil (Figure S1).…”
Section: Synthesis and Structure Of Heusler Single Crystalsmentioning
confidence: 57%
“…1(a)), all films display a characteristic 2× streaky reconstructed surface indicative of smooth epitaxial films. The 2× reconstruction is attributed to Sb dimerization which is well-known for antimonide half-Heusler surfaces [14].…”
Section: Resultsmentioning
confidence: 82%
“…We find that with decreasing photon energy (increasing surface sensitivity), the Sb 4d core level shows a secondary component with decreased binding energy that is localized to the surface. We attribute this secondary component to surface Sb-Sb dimerization [22]. A proposed model of the surface atomic structure is shown in Fig.…”
mentioning
confidence: 98%
“…For example, while the intrinsic carrier concentration of silicon is n i ∼ 10 10 cm −3 at room temperature, typical experimental carrier concentrations for semiconducting half Heuslers are typically ∼ 10 19 to 10 21 cm −3 due to defects and nonstoichiometry, which are difficult to control to better than 1% [21]. In select cases it has been shown that several Sb-containing Heuslersincluding CoTiSb [22,23], NiMnSb [24,25], LuPtSb [26], LaPtSb [27], and LaAuSb [28] -can be grown with an excess Sb flux, in which the ratio of Sb to (X + Y ) is self-limiting. Since the stoichiometry of one out of three elements is self-limiting, this can be called semi adsorption control.…”
mentioning
confidence: 99%
See 1 more Smart Citation